Technology enabled knowledge translation for ehealth : Principles and practice - Ho, Kendall (Healthcare Delivery in the Information Age, 2012)
Better health for the world's people is a moral imperative. Digital innovation linking the globe is a growing reality. Intersecting these critical phenomena, Technology-Enabled Knowledge Translation (TEKT) is opening up numerous arenas for improving access to care, upgrading quality of care, advancing health education, and reducing health inequities worldwide.   Technology-Enabled Knowledge Translation for eHealth surveys in depth the current status of major TEKT projects and its potential to contribute to future widespread health care refinements. In applications as varied as bioinformatics, youth e-mentoring programs, and electronic communities of practice, TEKT is shown as evolving toward larger humanitarian goals, addressing environmental concerns, and-in keeping with one of the earliest premises of the Internet-answering the salient question, "How global is e-health?" Contributors set out a well-rounded picture of TEKT use across health delivery platforms as the book:   Updates technological concepts in training, recordkeeping, and quality control. Provides extended examples of virtual collaboration between colleagues. Explores TEKT as a means of improving health outcomes in disadvantaged populations. Demonstrates applications of social media in qualitative research. Reports on TEKT projects from Mexico, China, and Brazil. Applies TEKT practice at the policy level.   Health care administrators as well as researchers in health care management, policy, and services will find Technology-Enabled Knowledge Translation for eHealth a leading-edge resource that stimulates action as well as interest.